Humanismo integral e desenvolvimento sustentável: somos mais do que iguais, somos todos irmãos - Zabala, Tereza Cristina (2016)
The theory of Integral Humanism developed by Jacques Maritain and assumed by the Social Doctrine of the Church and the United Nations in the Universal Declaration of Human Rights as a criterion for the dignity of the individual human person, collective and solidarity highlights the human being and their responsibilities in a solid relationship with the environment environment and nature as axis, purpose and effectiveness of sustainable development. In the current scenario of ecological crisis and the theme Development of the problem to achieve the aspect of Sustainable depends only on true solidarity mid humans and the Earth. The change is in how Jacques Maritain, in Integral Humanism recognizes and values the person starting from its creation to image and likeness of God, as a project of love and strength, able to compose a new social and environmental structure. The starting point is the concept of Integral Humanism, according to Jacques Maritain plan, whose conception of the human person gives it an Integral Development and calls for a sustainable development